Development of Computer Vision-based Visual Feedback Assistive Technology for Fine Motor Improvement in Children with Cerebral Palsy - Mawaddah, Tarisya; Sartinah, Endang Pudjiastuti; Wagino, Wagino (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Cerebral Palsy (CP) is a neuromotor condition that affects fine motor development, causing barriers to daily activities such as writing and grasping. This research develops an assistive technology that utilizes motion sensors to provide real-time visual feedback, which helps children understand and correct movements more effectively. The technology improves movement precision and coordination in motor skills, learner engagement, and structured monitoring of skill improvement. The uniqueness of this research lies in integrating computer vision technology with an interactive design that allows CP children to perform motor exercises and engage them in a more personalized and adaptive learning process. The Research and Development (R&D) method was used in the development, involving validating material experts, media experts, and educational practitioners. The results of media development show that assistive technology is feasible to use in improving the fine motor skills of children with cerebral palsy. Material experts stated an average value of 3.92, which was accumulated in percentage to 98.21%; media experts obtained results of 3.71, which was collected in percentage to 92.85%; and expert practitioners stated an average value of 3.93, which was accumulated in percentage to 98.43%. The assistive technology developed is worth testing in improving the fine motor skills of cerebral palsy children. This technology is expected to solve motor and coordination training issues at school and home. With a more interactive and fun approach, CP children can be more motivated to practice so that their motor skills can develop better.